Breast cancer patients' insurance status and residence zip code correlate with early discontinuation of endocrine therapy: An analysis of the ECOG‐ACRIN TAILORx trial. Issue 14 (1st April 2021) - Sadigh, Gelareh; Gray, Robert J.; Sparano, Joseph A.; Yanez, Betina; Garcia, Sofia F.; Timsina, Lava R.; Sledge, George W.; Cella, David; Wagner, Lynne I.; Carlos, Ruth C.
Abstract : Background: Early discontinuation is a substantial barrier to the delivery of endocrine therapies (ETs) and may influence recurrence and survival. The authors investigated the association between early discontinuation of ET and social determinants of health, including insurance coverage and the neighborhood deprivation index (NDI), which was measured on the basis of patients' zip codes, in breast cancer. Methods: In this retrospective analysis of a prospective randomized clinical trial (Trial Assigning Individualized Options for Treatment), women with hormone receptor–positive, human epidermal growth factor receptor 2–negative breast cancer who started ET within a year of study entry were included. Early discontinuation was calculated as stopping ET within 4 years of its start for reasons other than distant recurrence or death via Kaplan‐Meier estimates. A Cox proportional hazards joint model was used to analyze the association between early discontinuation of ET and factors such as the study‐entry insurance and NDI, with adjustments made for other variables. Results: Of the included 9475 women (mean age, 55.6 years; White race, 84%), 58.0% had private insurance, whereas 11.7% had Medicare, 5.8% had Medicaid, 3.8% were self‐pay, and 19.1% were treated at international sites. The early discontinuation rate was 12.3%. Compared with those with private insurance, patients with Medicaid (hazard ratio [HR], 1.53; 95% confidence interval [CI], 1.23‐1.92) and self‐pay patients (HR, 1.65; 95% CI, 1.25‐2.17) had higher early discontinuation. Participants with a first‐quartile NDI (highest deprivation) had a higher probability of discontinuation than those with a fourth‐quartile NDI (lowest deprivation; HR, 1.34; 95% CI, 1.11‐1.62). Conclusions: Patients' insurance and zip code at study entry play roles in adherence to ET, with uninsured and underinsured patients having a high rate of treatment nonadherence. Early identification of patients at risk may improve adherence to therapy. Lay Summary: In this retrospective analysis of 9475 women with breast cancer participating in a clinical trial (Trial Assigning Individualized Options for Treatment), Medicaid and self‐pay patients (compared with those with private insurance) and those in the highest quartile of neighborhood deprivation scores (compared with those in the lowest quartile) had a higher probability of early discontinuation of endocrine therapy. These social determinants of health assume larger importance with the expected increase in unemployment rates and loss of insurance coverage in the aftermath of the coronavirus disease 2019 pandemic. Early identification of patients at risk and enrollment in insurance optimization programs may improve the persistence of therapy. Abstract : Patients' insurance status and geographic residence play important roles in the persistence of endocrine therapy use. Early identification of patients at risk may improve adherence to therapy.